Radon-222 as a Tracer for Nonaqueous Phase Liquid in the Vadose Zone: Experiments and Analytical Model - Höhener, Patrick; Surbeck, Heinz (My University, 2004)
The potential use of the naturally occurring noble gas 222Rn as a tracer for vadose zone contamination by nonaqueous phase liquids (NAPLs) is studied experimentally and theoretically. n-Dodecane was chosen as the model NAPL. In batch experiments containing unsaturated alluvial sand, a 2.9-fold decrease of the steady-state 222Rn activity in soil gas was measured as a consequence of the increase in the volumetric NAPL content from 0 to 0.074. A one-dimensional analytical reactive transport model was developed that includes 222Rn production, gas-phase diffusion, partitioning, and radioactive decay. Radon-222 soil gas profiles were predicted for homogeneous and heterogeneous sandy profiles where NAPL contamination was restricted to selected depth layers. The resulting depth profiles document that the position of the NAPL has great influence on the 222Rn activity depth profile. An outdoor lysimeter experiment was performed using unsaturated alluvial sand contaminated by NAPL at depths from 1 to 1.2 m. In the lysimeter experiment, a spill of 2 L m−2 NAPL did not alter significantly the 222Rn profile, as predicted also by model calculations. We concluded that 222Rn can be used as a NAPL tracer in the vadose zone only at heavily polluted sites with uniform spatial 222Rn production.